Immunity of Toona ciliata M. Roem. var. australis (F.v.M.) C.DC and Khaya invorensis A. Chev. to attacks of Hypsipyla grandella Zeller in Turrialba, Costa Rica - Grijpma, Pieter (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In experimental plots at the Inter-American Institute of Agricultural Sciences, Turrialba, Costa Rica, Toona ciliata var australis (Australian Cedar) and Khaya ivorensis (Nigerian Mahogany) are not attacked by the Meliaceae borer (Hypsipyla grandella), whereas native Meliaceae such as Cedar (Cedrela spp.) and Mahogany (Swietenia spp.) are heavily attacked. In many tropical countries on other continents, these Latin American Meliaceae are not attacked or are less attacked by native Hypsipylas, although some countries report serious attacks.